(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2012)
In this work a flat plate collector was designed and manufactured with dimension of (100cm×160cm×20cm) and analyzed experimentally and theoretically. The designed FPC consist of Nine pipes with (2.223cm in diameter with 140cm long) welded above the plate to act as heat removal fluid passage ways. The flow inside the pipes can takes place by forced convection. However, certain energy absorbed by the plate is lost to atmosphere due to higher temperature of the plate. Effect of plate temperature on efficiency and top loss coefficient studied for different wind velocities and different air temperature. Effect of emissivity of absorber plate on top loss coefficient was estimated.The obtained result showed that the efficiency of FPC increase by 3%with the increase in ambient temperature by8 ̊C, the efficiency decrease with the increase in plate temperature and the top loss coefficient increase when the emissivity of absorber plate increase and when wind velocity increase. The comparison of result showed a good agreement.